THE EFFECT OF ORGANIZATIONAL CULTURE ON THE QUALITY OF ACCOUNTING INFORMATION SYSTEMS - Afriani, Afriani; Rapina, Rapina (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
In a company or organization, the quality of accounting information systems is very important and information technology is developing from time to time, thus demanding to work better and more integrated. organizational culture encourages employee creativity to improve transaction processing systems and integration of accounting information system components. lack of integration causes an untimely reporting system and poor quality of accounting information systems. this relates to corporate culture in issues related to innovation in the organization, relationships between staff, and organizational identification. But in reality, the quality of accounting information systems is still not good, therefore researchers are interested in research to examine the effect of organizational culture on the quality of accounting information systems. The method used in this research is a descriptive and verification method with a quantitative approach. The data source in this study is primary data with data collection techniques carried out by surveys using questionnaires. The population used in this study were employees of institutions in the field of education, namely Maranatha Christian University in Bandung. The results of this study indicate that organizational culture (X1) affects the quality of accounting information systems (Y1) in a company or organization.